(untitled) (Eurasian Journal of Philology Science and Education, 2016)
This article contains the facts about the first human migration from the African continent to the territory of the Altai Mountains and the formation of the culture of peoples of the Altaic language family. The author states that the wave of migration was continued, extending inland, paving the way from the Altai to Kolyma, over Chukotka to Alaska and beyond. It provides the scientific evidence that for centuries the ancient Turks made Altai their homeland; their culture, written language appeared in ancient times, spreading in all directions.